USE OF MACROECONOMIC FORECASTING AND PLANNING TOOLS IN THE CONDITIONS OF FINANCIAL MARKET DEVELOPMENT: A SYSTEMATIC APPROACH - Tarasenko, A. V. (The actual problems of regional economy development, 2024)
The article examines the theoretical foundations of the application of macroeconomic planning and forecasting tools in the context of financial market transformations. The purpose of the article is to develop theoretical provisions for the application of mechanisms of macroeconomic planning and forecasting according to the processes of state regulation of the financial market development. The European experience of macroeconomic planning and forecasting the development of the financial market has been studied. The importance of macroeconomic planning and forecasting measures for the implementation of the main functions of the financial market has been noted. It has been proposed to form a system of information and analytical support for macroeconomic planning and forecasting the development of the financial market, which is a set of information resources, means, methods, tools for its processing, necessary for the development and implementation of strategic and tactical directions of state regulation of the development of the financial market. The architecture of the specified system and its main tasks have been determined. It has been noted that the evaluation of the effectiveness of the system of information and analytical support for macroeconomic planning and forecasting takes place on the basis of monitoring, which is due to the long-term implementation of directions of state influence on the functioning of the financial market and the development of the financial system. The relationship between the processes of monitoring the development of the financial market based on the use of macroeconomic planning and forecasting tools has been studied. It has been proposed that the architecture of the system of information and analytical support for macroeconomic planning and forecasting of the development of the financial market makes it possible to distinguish the following functional subsystems: strategic planning subsystem, information collection and assessment subsystem, motivation subsystem of financial relations subjects, monitoring subsystem. It provides for measures to assess the effectiveness of the proposed program measures for the development of the financial market, the achievement of forecasted indicators and the development of solutions for the leveling of possible deviations and the minimization of risks.